The effect of specific surface area of macro fibers on energy absorption capacity of concrete. Issue 5 (4th May 2019) - Rostami, Rouhollah; Zarrebini, Mohammad; Sanginabadi, Khaled; Mostofinejad, Davood; Abtahi, Sayyed Mahdi; Fashandi, Hossein
Abstract: Energy absorption capacity is the salient property of concrete. Reinforcement of concrete with macro fibers is one of the techniques that has led to enhancement of this important feature of concrete. However, the effect of specific surface area of melt-spun polypropylene macro fibers has hardly been studied so far. In this work, the effect of this parameter on mechanical behavior of fiber reinforced concrete (FRC) was investigated. Diameter of macro fibers was varied by changing the melt feeding rate and fiber draw ratio. Changes in fibers diameter affect fibers specific surface area, which in turn influences the adhesion of fibers to the matrix in FRCs. In order to evaluate the FRCs behavior, bending tests were conducted and the area under load-displacement curves was studied. It was found that increase in specific surface area of fibers results in considerable increase in energy absorption capacity of the FRCs. Concrete reinforced with the larger diameter fibers exhibited 6× energy absorption capacity than the reference sample. This was found to be in line with the 14× energy absorption capacity of sample which was reinforced by smaller diameter fibers. This was attributed to the increase in total contact area between the finer fibers and the matrix as a direct consequence of the increase in number of fibers for a given fiber volume fraction.